Reka bentuk model program perkembangan profesionalisme guru Malaysia / Abd Khalil Adnan - Abd Khalil, Adnan (2017)
The purpose of this study is to design a model of professional development program for Malaysian teachers. In particular, the implementation of this study was based on the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) by Michael Molenda (2003) which includes three phases. The need analysis phase identifies the current needs for developing the model. The design phase develops a model of professional development program for Malaysian teachers. Finally, the evaluation phase evaluates the prototype model. To achieve the objectives of the first phase, the questionnaire data were collected from 185 teachers of high and low performing schools. The data were analyzed using descriptive statistics such as percentage, mean and standard deviation. In the design phase, the Delphi study which had reached consensuses among 18 experts in human resource management developed a model of teaching professional development programs. Members of an expert panel composed of policy makers and practitioners were interviewed. The interview data that were analyzed using thematic analysis established items agreed on by the expert panel in the second round of the Delphi study. The second round of Delphi study data were processed using Fuzzy Delphi analysis. In addition, the prototype model was evaluated using a survey study in the evaluation phase. Viewpoints of 300 teachers from 20 boarding schools in Central Zone and South Zone were used to identify the level of teaching professional development programs and the differences in implementation between the zones. Data were analyzed using descriptive statistics such as percentage, mean and standard deviation, and inferential statistics (Mann-Whitney U and Structural Equation Modelling). The findings of the need analysis phase were to match the needs of the model when 185 teachers of high and low performing schools agreed with the design of this model when the mean score was more than 4.0. The Delphi study found that all 18 experts reached consensus on the items to be included in the model as its content. Consensus among the expert panel was established when the score of Threshold was d=≤0.2 and the percentage agreement was ≥75%. This phase found four key dimensions as follows and 310 items that made up the strategies of teaching professional development program: program objectives, program content, program delivery strategy and program evaluation method. The evaluation phase found that the teaching professional development program of the schools was high when the mean score was more than 4.0. The study also found that there was a significant difference between the two school zones in implementing the program when p<0.05. Meanwhile the correspondence between prototype model proposed by the research data were confirmed when NFI, RFI, IFI, TLI, CFI value > .90 and RMSEA <.08). The implication of this study implies there is a need to develop a model of professional development program for Malaysian teachers that is based on the local context because of the different needs and problems in every organisation.